2021
DOI: 10.1111/polp.12447
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of a politicized public service system: Perspectives of politicians, public servants, and political experts

Abstract: Politicization has different consequences for public administration and public services in different countries. This study seeks to identify the consequences of politicization in the Iranian public service. After reviewing the theoretical foundations of politicization, the authors reflect on different researchers' and political experts' views about the consequences of politicization. In the first phase of the study, qualitative data were gathered and categorized into structural, content-behavioral, and environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In totalitarian regimes, such as the one in Iran, a whole array of socialization agents is worked on or mobilized to help young people gain an understanding of the political world. Among these agents are the family, the education system, the mass media, and other social institutions that the government uses to serve its agenda (Peters et al, 2022). Furthermore, some studies such as the one done by Greenstein (2017) suggested that the children's first conception of political authority is more based on emotion than cognition.…”
Section: Youth and Political Socializationmentioning
confidence: 99%
“…In totalitarian regimes, such as the one in Iran, a whole array of socialization agents is worked on or mobilized to help young people gain an understanding of the political world. Among these agents are the family, the education system, the mass media, and other social institutions that the government uses to serve its agenda (Peters et al, 2022). Furthermore, some studies such as the one done by Greenstein (2017) suggested that the children's first conception of political authority is more based on emotion than cognition.…”
Section: Youth and Political Socializationmentioning
confidence: 99%
“…Voters adhere to a political party to have access to jobs in public institutions (Peters and Bianchi, 2023), and this is a form of vote buying when voters are promised public jobs (Volintiru, 2015). Peters et al (2022) argue that the goal of politicization in developing countries is to provide jobs for party members and loyal people, while in developed countries, politicization is used to control the policy-making process.…”
Section: Goals Of Politicizationsmentioning
confidence: 99%
“…Overall, politicization is a pervasive issue that lowers the capabilities of public employees, corruption, and lowers trust in public institutions and political leaders (Peters et al, 2022). When political appointments duplicate the existing positions, the government becomes big, loses resources, and the work commitment of non-political civil servants lowers.…”
Section: Consequences Of Politicizationmentioning
confidence: 99%
“…Taken together, we thus anticipate that this volume will offer a retrospective snapshot of the history of the journal that promises to be as interesting in its own right as it is useful for mapping areas for future research.We hope you enjoy the articles in this issue of P&P which, as is now customary, span a multitude of policy questions from a comparative international perspective. In this issue, we traverse the subfields of energy infrastructure (You et al, 2022), public service and policy experts in the Middle East (Peters et al, 2022) and China (Shen et al, 2020), environmental accidents in China (Zang, 2022), natural resource conservation in the United States (Dunning, 2022) and Africa (Ayanoore & Hickey, 2022), referendum rules in New Zealand (McKay, 2022), and problems with the South Asian Association for Regional Cooperation (SAARC) (Bishwakarma & Zongshan, 2022). Keep safe and well in the ongoing pandemic and we look forward to your continued article submissions as well as your P&P past article reviews (which will receive expedited peer review…”
mentioning
confidence: 99%